2000
DOI: 10.4315/0362-028x-63.4.495
|View full text |Cite
|
Sign up to set email alerts
|

A Method of Assessing the Efficacy of Hand Sanitizers: Use of Real Soil Encountered in the Food Service Industry

Abstract: In many outbreaks of foodborne illness, the food worker has been implicated as the source of the infection. To decrease the likelihood of cross-contamination, food workers must clean and disinfect their hands frequently. To ensure their effectiveness, hand disinfectants should be tested using rigorous conditions that mimic normal use. Currently, several different methods are used to assess the efficacy of hand disinfectants. However, most of these methods were designed with the health care worker in mind and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 9 publications
2
35
2
Order By: Relevance
“…Efficacy of AIHS in reducing microbial populations on hands (Miller et al 1994;Paulson 1994;Charbonneau et al 2000;Kramer et al 2002) or fingernails (Mahl 1989;McNeil et al 2001) has been studied previously with somewhat different conclusions from what are reported here. To simulate actual-use conditions, the volunteers where not instructed to concentrate on fingernail areas when rubbing with alcohol gel.…”
Section: Resultscontrasting
confidence: 66%
See 2 more Smart Citations
“…Efficacy of AIHS in reducing microbial populations on hands (Miller et al 1994;Paulson 1994;Charbonneau et al 2000;Kramer et al 2002) or fingernails (Mahl 1989;McNeil et al 2001) has been studied previously with somewhat different conclusions from what are reported here. To simulate actual-use conditions, the volunteers where not instructed to concentrate on fingernail areas when rubbing with alcohol gel.…”
Section: Resultscontrasting
confidence: 66%
“…Statistical significance P £ 0.05 indicated by differing letters (A, B, C, D and X). This inability to remove organic residues has also been reported in other studies (Miller et al 1994;Paulson 1994;Charbonneau et al 2000;Kramer et al 2002) and was likely responsible for the low efficacy of AIHS. It should be noted that testing procedures in the two studies reporting greater efficacy with AIHS were significantly different from those used in this study.…”
Section: Figuresupporting
confidence: 72%
See 1 more Smart Citation
“…For all tests in this study, volunteers contaminated their hands (both left and right) by manipulating a fresh, uncooked chicken, as recommended by Charbonneau et al. (2000).…”
Section: Methodsmentioning
confidence: 99%
“…While hand sanitizers may be important in limiting the spread of contagious disease, they are not effective against anthrax and Clostridium difficile . Hand sanitizers are not good at removing visible dirt from the hands and are best used on clean hands that might contain nonvisible dirt . While hand sanitizers can solubilize intercellular lipids, a study in healthcare workers demonstrated better skin condition with the use of hand sanitizers as opposed to frequent hand washing…”
Section: Cleanser Formulationsmentioning
confidence: 99%